Pemikiran Reformis Rashid Rida dan Muhammad Abduh: Analisis Komparatif Dua Tokoh Pembaharuan Islam Modern dalam Pendidikan Islam di Indonesia - Nur Mufidah; Rasmansyah Rasmansyah; Rina Setyaningsih; Jihan Azzahra; Nabila Safitri; Gentam Gemuruh (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines two major figures of modern Islamic reformism, Muhammad Abduh and Rashid Ridha, and how their thoughts shaped the face of Islamic education in Indonesia. Through qualitative research with a historical-comparative approach, We found that while both men shared a vision of reform, their views on modernity were very different. Abduh tended to be more open in accepting Western progress while still maintaining Islamic values, while Ridha was more cautious and prioritised purifying Islamic teachings from outside influences. These two schools of thought then coloured the journey of Indonesian Islamic organisations such as Muhammadiyah and Persis, which still feel their impact today. This research suggests the need for a synthesis of the two approaches in developing Islamic education that is authentic yet responsive to the challenges of the times.